An Assessment of the use of the ISO 50001 Certified Energy Management Systems by Airports - Baxter, Glenn (International Journal of Environment, Agriculture and Biotechnology, 2022)
This study has examined the airports located throughout the world that have implemented an ISO 50001 certified Energy Management System (EMS). The research used an in-depth instrumental case study research design. The study period was from 2011 to 2022. The study found that ISO 50001 certified Energy Management Systems are increasingly being adopted by airports and these systems are playing a key role in their environmental management. Airports located in China, Cyprus, Hong Kong, Europe, India, Turkey, Sweden, United Kingdom, United States of America have implemented ISO 50001 certified Energy Management Systems since the inception of this standard in 2011. ISO 50001 certified Energy Management Systems have been implemented by hub airports, by airports that service both domestic and international airlines services, and by smaller regional airport. The case study found that airports are using their ISO 50001 certified Energy Management System to optimize their energy efficiency. These airports have implemented a very wide range of energy conservation measures, including the use of light emitting diode (LED) systems, the electrification of ground service equipment and vehicles, the installation of electric vehicle charging stations, the installation of photovoltaic (PV) solar systems, building heating and cooling systems optimization, and the optimization of energy for plant and equipment. The case study also highlighted the importance that the airports using an ISO 50001 certified Energy Management System are placing on the use of more environmentally friendly renewable energy sources.